2020
DOI: 10.1002/cncr.33203
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 23‐valent pneumococcal polysaccharide vaccination on the frequency of pneumonia‐related hospitalization and survival in elderly patients with prostate cancer: A seven‐year nationwide matched cohort study

Abstract: BACKGROUND: The 23-valent pneumococcal polysaccharide vaccine (PPSV23) is indicated for adults who have a high risk of pneumonia; however, its effectiveness in patients with prostate cancer who are at a risk of pneumonia because of age and cancer treatments, including androgen-deprivation therapy, is unknown. METHODS: Between 2000 and 2010, 38,735 patients with prostate cancer were diagnosed in Taiwan. After exclusions and exact matching for age, previous pneumonia, and influenza vaccination, 2188 vaccinated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…After applying the eligibility criteria, 102 studies remained, forming the evidentiary basis for the guideline recommendations: 24 systematic reviews, 11, 14 RCTs, 6,[44][45][46][47][48][49][50][51][52][53][54][55][56] and 64 nonrandomized studies. [85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118][119][120] The ...…”
Section: Characteristics Of Studies Identified In the Literature Searchmentioning
confidence: 99%
“…After applying the eligibility criteria, 102 studies remained, forming the evidentiary basis for the guideline recommendations: 24 systematic reviews, 11, 14 RCTs, 6,[44][45][46][47][48][49][50][51][52][53][54][55][56] and 64 nonrandomized studies. [85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118][119][120] The ...…”
Section: Characteristics Of Studies Identified In the Literature Searchmentioning
confidence: 99%
“…PPSV23 vaccination significantly reduced the risk of pneumonia hospitalization, with an IRR of 0.880 (p=.04) and demonstrated a significantly better overall survival in the vaccinated cohort than in the unvaccinated cohort (p=.001) [ 76 ]. Finally, Li et al confirmed that the risk of pneumonia-related hospitalization in patients with prostate cancer aged ≥75 years was 0.48 times lower in the PPSV23 vaccination group than that in the unvaccinated one (adjusted IRR, 0.48; p = .046) [ 77 ].…”
Section: Influenza Vaccines and Cancer-related Outcomes During Icismentioning
confidence: 99%
“…It was documented that there was no significant difference in age, sex, region, ambulatory care, and inpatient expenditures between the LGTD2005 and NHI programs. Details regarding LGTD2005 and Taiwan's national health insurance claims data have been reported in our previous work (23,(25)(26)(27)(28).…”
Section: Data Sourcementioning
confidence: 99%